Constructing a small modular stellarator in Latin America - Asenjo, J.; Carvajal-Godínez, Johan; González-Gómez, J.; Soto-Soto, C.; Piedra, C.; Barillas-Mora, Laura; Mora-Meléndez, Jaime; Otárola-Zúñiga, Carlos; Zamora-Picado, Esteban; Vargas-Blanco, Iván (Institute of Physics Publishing, 2015)
This paper aims at briefly describing the design and construction issues of the stellarator of Costa Rica 1 (SCR-1). The SCR-1 is a small modular stellarator for magnetic confinement of plasma developed by the Plasma Laboratory for Fusion Energy and Applications of the Instituto Tecnológico de Costa Rica (ITCR). SCR-1 will be a 2-field period small modular stellarator with an aspect ratio > 4.4; low shear configuration with core and edge rotational transform equal to 0.32 and 0.28; it will hold plasma in a 6061-T6 aluminum torus shaped vacuum vessel with an minor plasma radius 54.11 mm, a volume of 13.76 liters (0.01 m3), and major radius R = 238 mm. Plasma will be confined in the volume by on axis magnetic field 43.8 mT generated by 12 modular coils with 6 turns each, carrying a current of 767.8 A per turn providing a total toroidal field (TF) current of 4.6 kA-turn per coil. The coils will be supplied by a bank of cell batteries of 120 V. Typical length of the plasma pulse will be between 4 s to 10 s. The SCR-1 plasmas will be heated by ECH second harmonic at 2.45 GHz with a plasma density cut-off value of 7.45 × 1016 m-3. Two magnetrons with a maximum output power of 2 kW and 3 kW will be used. © Published under licence by IOP Publishing Ltd.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84938118149&partnerID=40&md5=1d385f1e177901beaf6f30228abdd67b
Keywords: Plasma; Magnetismo; Potencia eléctrica; Research Subject Categories::TECHNOLOGY::Engineering physics::Plasma physics with fusion